(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
This article explores the power manifestations of tyrannies in Eraclea Pontica, and it highlights the links between individual tyrants and the divine sphere. The article starts by investigating the colonial foundation of the city of Eraclea Pontica carried out by the Dorians. Then, the study explores the relationships between the city and the philosophical schools of Athens, and therefore, the article focuses on tyrannies and the power manifestations in Eraclea Pontica, bringing out the connections these had with both the Siciliotan tyrannies and the chtonic deities in the statement of the leadership. Finally, the study examines the Amatris’ reign, the territorial development, and the foundation of a new city by Amastris.